2004
DOI: 10.1016/s0896-6273(04)00222-3
|View full text |Cite
|
Sign up to set email alerts
|

Disabled-1-Regulated Adhesion of Migrating Neurons to Radial Glial Fiber Contributes to Neuronal Positioning during Early Corticogenesis

Abstract: Disabled-1 regulates laminar organization in the developing mammalian brain. Although mutation of the disabled-1 gene in scrambler mice results in abnormalities in neuronal positioning, migratory behavior linked to Disabled-1 signaling is not completely understood. Here we show that newborn neurons in the scrambler cortex remain attached to the process of their parental radial glia during the entire course of radial migration, whereas wild-type neurons detach from the glial fiber in the later stage of migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
145
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(156 citation statements)
references
References 47 publications
10
145
0
1
Order By: Relevance
“…Five days later, at E19.5, Dab1 shRNA neurons were significantly deeper than matched vector controls (P = 0.011) (Fig. 8A,B,D), as expected (Hammond et al 2001;Tabata and Nakajima 2002;Sanada et al 2004;Olson et al 2006). Dab1 shRNA neurons were also slightly deeper than controls at E17.5 (data not shown).…”
Section: Dab1 Role In Cul5-regulated Neuron Positioningsupporting
confidence: 69%
See 1 more Smart Citation
“…Five days later, at E19.5, Dab1 shRNA neurons were significantly deeper than matched vector controls (P = 0.011) (Fig. 8A,B,D), as expected (Hammond et al 2001;Tabata and Nakajima 2002;Sanada et al 2004;Olson et al 2006). Dab1 shRNA neurons were also slightly deeper than controls at E17.5 (data not shown).…”
Section: Dab1 Role In Cul5-regulated Neuron Positioningsupporting
confidence: 69%
“…In addition, in utero electroporation of Dab1 shRNA at E18 caused neurons to lag behind their siblings, and their leading processes were less developed (Olson et al 2006). In utero infection of wild-type or Dab1 mutant brains with retroviruses encoding phosphorylation site mutants of Dab1 allowed the role of Dab1 phosphorylation in the movement of individual neurons to be tested (Sanada et al 2004). Dab1 mutants that were unable to rescue movement were found deeper in the cortical plate and were closer to their radial glia guides than control neurons.…”
Section: Dab1 Role In Cul5-regulated Neuron Positioningmentioning
confidence: 99%
“…The distinction between radial and tangential migration may be blurred somewhat in the RMS, as neurons undergo chain migration but through a substrate of glial guidance. A similar requirement for LIS1 and components of the reelin pathway in both radial and tangential migration have reported 18,[60][61][62] .…”
Section: As a Regulator Of Radial And Tangential Migrationsupporting
confidence: 65%
“…3D ; compare lanes 4-6). For neuronal migration, Tyr-phosphorylated DAB1 (pY-DAB1) is essential, because it is compromised by expression of the "5YF" DAB1 mutant, in which fi ve Tyr residues are replaced with Phe, a structurally similar but nonphosphorylatable aa ( 8 ). In the RKO cells expressing 5YF-DAB1, we found that the pY-ABL1b level remained low ( Fig.…”
Section: Research Articlementioning
confidence: 90%